Ecotype variations and endophytic fungal diversity of aquatic angiosperm: A case study with Lagenandra toxicaria Dalz - Pooja, P; Lekshmi, E K; Pradeep, N S (Plant Science Today, 2025)
A study on Lagenandra toxicaria ecotypes from Kottavayal, Pakkom and Mattilayam investigated the morphological variations in response to different pot sizes. The experiment employed a completely randomized design with three replicates to ensure reliable results. The researchers used statistical analyses to examine ecotype variations. The Duncan multiple range test calculated the mean separation at a 5% probability level. The study employed cluster analysis using the unweighted pair-group method of arithmetic averages and principal component analysis to identify and visualize the relationships among the samples. Cluster analysis revealed three distinct groups among the ecotypes, thereby shedding light on their relationships. The Kottavayal, Pakkom and Mattilayam ecotypes formed separate clusters, indicating their unique morphological characteristics. These findings provide valuable insights into the morphological diversity of Lagenandra toxicaria ecotypes and their adaptability to different environments. The endophytic fungal diversity details from this study revealed a high level of diversity, with 1408 isolates belonging to 12 families. The highest number of fungal isolates was observed during the summer. The present study revealed that the diversity was higher in the roots than in the leaves, higher than that of the rhizome of Lagenandra toxicaria. Colonization rate, Simpson’s diversity index and Shannon-Wiener’s diversity index were higher in root samples than in leaf and rhizome samples. MANOVA analysis revealed highly significant effects (p < 0.01) of individual factors, including location, season and plant species and their interaction effects. These results indicate that endophytic fungal diversity is significantly influenced by these factors and their interactions at a significance level of 1%.